Case Report: Osteosclerotic metaphyseal dysplasia with optic nerve involvement and progressive osteonecrosis of the jaw due to a novel LRRK1 mutation - Pieridou, Chariklia; Sabir, Ataf; Lancashire, Jonathan; Liang, Yifan; McMillan, Kevin; Shaw, Nick; Uday, Suma (Frontiers in Endocrinology, 2023)
Background: Osteosclerotic metaphyseal dysplasia (OSMD, OMIM 615198) is an extremely rare autosomal recessive osteopetrosis disorder resulting in a distinctive pattern of osteosclerosis of the metaphyseal margins of long tubular bones. To date, only thirteen cases have been reported (eight molecularly confirmed). Five homozygous sequence variants in the leucine-rich repeat kinase 1 (LRRK1) gene have been identified to cause OSMD. We present two male siblings with OSMD with a novel LRRK1 variant.The index case, now aged 6 years, was referred aged 9 months when diffuse sclerosis of the ribs and vertebral bodies, suggestive of osteopetrosis, was incidentally identified on a chest radiograph for suspected lower respiratory tract infection. Parents were consanguineous and of Pakistani origin. Further evaluation revealed developmental delay, nystagmus with bilateral optic nerve hypoplasia and severe visual impairment. Skeletal survey confirmed typical changes of OSMD, with widespread diffuse sclerosis and Erlenmeyer flask deformity of long bones.His older sibling, now aged 12 years, was 7 years at the time of referral and had similar clinical course and skeletal findings. Additionally, he had a chronic progressive osteonecrosis of the left mandible that required debridement, debulking and long-term antibiotics. Skeletal survey revealed findings similar to his sibling.Neither sibling had significant skeletal fractures or seizures. Unlike most previous reports suggesting sparing of the skull and lack of visual impairment, our patients had evidence of osteosclerosis of the cranium. Genetic screening for the common autosomal recessive and dominant pathogenic variants of osteopetrosis was negative. Whole Exome Sequencing (WES) followed by Sanger sequencing, identified a novel homozygous LRRK1 c.2506C>T p.(Gln836Ter) nonsense variant predicted to result in premature truncation of LRRK1 transcript.Our cases confirm the autosomal recessive inheritance and expand the spectrum of genotype and phenotype of OSMD reported in the literature. Increasing reports of LRRK1 variants in this phenotype raise the question of whether LRRK1 should be included in targeted osteopetrosis panels. Bone histology in previous cases has shown this to be an osteoclast rich form of osteopetrosis raising the possibility that haematopoietic stem cell transplantation may be an appropriate treatment modality.